2018
DOI: 10.1101/358416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KRASG12D and TP53R167H Cooperate to Induce Pancreatic Ductal Adenocarcinoma in Sus Scrofa Pigs

Abstract: Although survival has improved in recent years, the prognosis of patients with advanced pancreatic ductal adenocarcinoma (PDAC) remains poor. Despite substantial differences in anatomy, physiology, genetics, and metabolism, the overwhelming majority of preclinical testing relies on transgenic mice. Hence, while mice have allowed for tremendous advances in cancer biology, they have been a poor predictor of drug performance/toxicity in the clinic. Given the greater similarity of sus scrofa pigs to humans, we eng… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Porcine tumor sections were also extensively stained positive with Masson's trichrome (Additional file 1: Fig. S8c), indicating that a desmoplastic tumor stroma developed similar to human patients with PDAC [42]. IHC staining of pancreatic head and tumor sections showed that pERK (a KRAS activation effector), PCNA (a proliferative marker), CK19 (a ductal origin marker), E-cadherin (an epithelial lineage marker), and vimentin (a mesenchymal marker) were expressed in the tumor stroma (Fig.…”
Section: Validation Of the Effectiveness Of In Vivo Genome Editing An...mentioning
confidence: 90%
“…Porcine tumor sections were also extensively stained positive with Masson's trichrome (Additional file 1: Fig. S8c), indicating that a desmoplastic tumor stroma developed similar to human patients with PDAC [42]. IHC staining of pancreatic head and tumor sections showed that pERK (a KRAS activation effector), PCNA (a proliferative marker), CK19 (a ductal origin marker), E-cadherin (an epithelial lineage marker), and vimentin (a mesenchymal marker) were expressed in the tumor stroma (Fig.…”
Section: Validation Of the Effectiveness Of In Vivo Genome Editing An...mentioning
confidence: 90%